Challenges of market definition and price discrimination in preparing strategy of negotiations. (18th February 2022) - Peleckis, Kęstutis; Peleckienė, Valentina; Peleckis, Kestutis; Leonavičienė, Edita
The extent of competition in the market affects the balance of bargaining power of market participants. When price discrimination is low, it increases consumer welfare - that is, if the price does not correspond to the evaluation of each product by the consumer, then discrimination allows for additional consumers to buy the product at a price, which is lower than the one they would have liked to pay for it. This often results in negative consequences for both buyers and suppliers. The aim of the article is to analyse the existing theory and practice of negotiation strategy in a complex way, at different levels of competition, to reveal possibilities to develop and implement negotiating strategies, taking into account the problems of price discrimination. The article deals with the problem - there are not enough tools in the negotiation theory to help develop negotiation strategies with different levels of competition and price discrimination problems. The paper analyses the mathematical model of oligopoly. This model explores the feasibility and effectiveness of negotiation strategy preparation in the face of distorted market competition.